A dynamic theory of optimal capital structure and executive compensation - Atkeson, Andrew 1961-; Cole, Harold L. 1957- (National Bureau of Economic Research, 2005)
"We put forward a theory of the optimal capital structure of the firm based on Jensen's (1986) hypothesis that a firm's choice of capital structure is determined by a trade-off between agency costs and monitoring costs. We model this tradeoff dynamically. We assume that early on in the production process, outside investors face an informational friction with respect to withdrawing funds from the firm which dissipates over time. We assume that they also face an agency friction which increases over time with respect to funds left inside the firm. The problem of determining the optimal capital structure of the firm as well as the optimal compensation of the manager is then a problem of choosing payments to outside investors and the manager at each stage of production to balance these two frictions"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Corporations -- Finance -- Econometric models